Ação Popular como instrumento da cidadania - Lima, Ana Clara Viana Soares (2019)
The purpose of this dissertation is to analyze the exercise of citizenship through Popular Action in Brazil. The objective is to research on the concept of democracy since the emergence of the Polis and the evolution of the word, effectively, in the daily life of the citizen. In addition, to present the appearance of the Popular Action, its effectiveness and applicability from the point of view of the Federal Constitution, Code of Civil Procedure and Law 4717/65. It is necessary to demonstrate the constancy of the Popular Action in the Brazilian Constitutions and how the passage of time has modified the society. The Popular Action is, mainly, an instrument of control of the Public Administration, since under the power of the administered are diffuse and collective goods. That is, the popular representative proceeds from the impersonal nature of the interest defended, it is the defense of the public thing and the people